(untitled) (Mustansiria Dental Journal, 2024)
Osteoarthritis (OA) is a degenerativejoint disease marked by progressive loss of articular cartilage and damage of bony components. The clinical features include ;joint pain, crepitus and limitation of movement. The exact cause of OA is unknown however some authors consider it as a multifaetorial disease. The age and over usage are the most common tactors, in addition to race and sex. ln case of temporomandibular joint(TMJ), traumatic occlusion, and over load caused by parafunctions are additional factors. The purpose ofthis investigation was to study the TMJ) arthropathy among a group of Iraqi patients previously diagnosed as having( .OA One hundred patients with OA are used in this study. They were examined .clinically and radiographically for effects of systemic OA on TMJ Results of the study revealed that 39% of patients with OA have TMJ lesions of different degrees ranged between osteophytes, diminusion of joint space and bone .distruction ofglenoid fossa and head of condyle Dental management of temporomandibular joints affected with OA usually aim to suppress the active disease, preserve functions, prevent deformity and relieve pain. Early detection of the disease and early commencement of management greatly i reduce joint destruction and improve prognosis. Results of this study indicated that l1% of patients had only TMJ lesions, with no other joints lesions. Because of difficulty of interpretation of TMJ radiographs we suggest criteria for radiographic diagnosis of osteoarthritis ofthe TMJ